Asking for support. The case of families with children suffering cancer - Cacante C, Jasmín V; Arias Valencia, María Mercedes (Investigación y Educación en Enfermería, 2009)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective: to describe the process of support that families of children with cancer experience during their oncology illness. Methodology: a study with grounded theory approach carried out by 18 interviews to mothers in different moments of the child illness, during 2005 and 2006. Results: families assume the larger part of the care burden, especially the mothers activating support networks, arousing sympathy and looking for help until they find it. Conclusions: the needs and forms of support change according to the phase of the illness. Observing the formal and informal support networks we find them insufficient and accordingly a solidarity network should emerge. In any case mothers are the principal support of the suffering children.